ANALISIS PENYELESAIAN SENGKETA TANAH WARISAN MELALUI JALUR MEDIASI TINGKAT DESA - Nur Wahid; Abdul Halim Talli; Patimah (Qadauna: Jurnal Ilmiah Mahasiswa Hukum Keluarga Islam)
Abstract This research is an attempt to make observations related to "Analysis of Inherited Land Dispute Resolution through Mediation Path at the Village Level Case Study (Mamampang Village, Kec. Kuncio Pao, Gowa Regency) to know several series of procedures for resolving inheritance land disputes in Mamampang Village. This type of research is empirict law by tracing some factual data about the problem that is the subject of the research, namely the settlement of inheritance land disputes in Mamampang village. Furthermore, the approach in this research is a normative syar'i theology approach. the data collection method used is data observation techniques (field studies) on the process of resolving inheritance land disputes in Mamampang village which describes the process of systematically handling disputes through mediation processes and applicable regulations. Therefore, this study obtains a result in the process of resolving inheritance land disputes in Mamampang village. First, an overview of the legal basis used in the settlement of inheritance land disputes in Mamampang Village, second, a description of the process and factors that influence the process of resolving inheritance land disputes through the mediation in Mamampang Village, third, a picture of the perspective of Islamic law in resolving inheritance land disputes in Mamampang Village. Keywords; settlement, inheritance disputes, mamampang village, mediation.